Fourier Transform Infrared and Chromatographic Fingerprint of Essential Oil from Pogostemon benghalensis (Burm. F.) Kuntze (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
The purpose of the present research work is to investigate the functional group and category of secondary metabolites present in the essential oil (Eo) from Pogostemon benghalensis using Fourier transform infrared (FTIR) spectrometry, HPTLC and GC-MS technique. FTIR measures the vibrations of bonds within the functional groups and yields a spectrum that can be considered as biochemical or metabolic fingerprint of the plant product. Using FTIR spectra, it is possible to find out the minor changes of primary and secondary metabolic characteristic functional groups which are responsible for their biological feature of the species. FTIR is a nondestructive, cost effective, user and eco-friendly tool. Pogostemon benghalensis, a wild relative of P. cablin, the highly utilized and adulterated medicinal herb by the native people for the extraction of essential oil Patchouli. The fresh leaves were subjected to hydro distillation for the extraction of the essential oils and were analyzed using the above techniques. The FTIR spectral lines have shown diverse unique peaks of functional groups. FTIR confirmed the volatile compounds and indicated by their functional groups of the essential oils such as C-H (Alkene), C-H (aromatic) and C=C. Similarly, the analysis proved the presence of alcohols, p-substituted alcohols or phenols, alkanes, alkynes, alkenes, aldehyde, ester, ether, aliphatic amines, carboxylic acids, aromatics, ketones, disulphide, alkyl halides, halogen, and nitro derivatives. The intensity and estimation of predominant volatiles were analysed by HPTLC, which showed 8 peaks with max Rf values ranged from 0.07 to 0.96. Further, the Eo was fractionated by with GC-MS technique and identified 41 volatile fractions in the oil. Thus, the obtained data provides the biochemical profiles with overlapping signals of a wide array of molecules that are present in the cells. So, the usage of essential oils in pharmacy, cosmetology and aromatherapy industries may be substantiated. Further advanced spectroscopic analysis is required to identify the structure and nature of active principles present in the Eo.